Fatores biomecânicos e complicações protéticas : estudo prospectivo em próteses totais fixas implantossuportadas - Coltro, Maria Paula de Lima (2016)
Failures in implant supported fixed complete dentures may be related to the biomechanical factors and structural quality of the prostheses. The aim of this prospective cohort study was to investigate the influence of the biomechanical and clinical factors on failures and complications observed in implant supported fixed complete dentures. The data were collected at baseline and 6, 12, 24 and 36 months after delivery of the definitive prostheses through anamneses, physical examination and measurements of maximal bite force, presence and intensity of the bruxism, quality of life (OHIP-14), distribution of the occlusal contacts and technical quality of the metallic framework. Statistical analysis was performed using the Kaplan-Meier survival analysis, multivariate analysis by a Cox regression model and a paired t-test. The convenience sample consisted of 69 patients rehabilitated with 72 fixed complete dentures with up to 47 months of follow-up. Thirteen fixed complete dentures failed (18%), occurring avulsion or fracture of the artificial denture teeth. The main results were; 1) high success index of the treatment with 100% implant survival rate in 36 months and occurrence of 18% of repairable failures in prostheses. 2) presence of bruxism or high maximal bite force do not negatively influence the occurrence of the failures. 3) the design of the metallic framework (insufficient height of the retentive pins) is the risk factor for the failures. No association was found between failures and gender, body mass index, thickness of the aesthetic coating, type of the antagonist arch or superior/inferior arch. The results suggest that a better standardization of metal framework construction is necessary, because insufficient height of the retentive pins of the denture teeth was the main factor related to the failures in evaluated prostheses. It is possible to control this factor in the laboratory and in the clinic to reduce the risk of failure and increase the longevity of the prostheses. Moreover, occlusal adjustments should be carefully observed, because the failures appear to occur more on the overloaded segment of the arch.